Quantification of left ventricular fibrosis in arrhythmic mitral valve prolapse patients: comparison of different semi-automated techniques assessed by cardiac magnetic resonance. (3rd October 2022) - Cecere, A; Cipriani, A; Ravagnin, A; Graziano, F; Brunetti, G; De Conti, G; Motta, R; De Lazzari, M; Iliceto, S; Perazzolo Marra, M
Abstract: Background: Left ventricular (LV) fibrosis has a key role in arrhythmogenesis in mitral valve prolapse (MVP) patients. Cardiac magnetic resonance (CMR) demonstrated able to clearly identify LV fibrosis with the post-contrast late gadolinium enhancement (LGE) images. Despite the pivotal role of LV fibrosis in the arrhythmogenesis, a quantification and identification of reproducible method able to accurately measure LGE in arrhythmic MVP patients has not been recognized. Purpose: We aimed to measure and compare different semi-quantitative methods for LGE quantification assessed by CMR, in order to identify the most reproducible one, in arrhythmic MVP patients. Methods: 66 arrhythmic MVP patients with normal systolic function and without significant regurgitation were enrolled. Semi-automated gray-scale thresholding technique using full with at half maximum (FWHM) and 2, 3 and 5 standard deviation (SD) above the remote myocardium were used and compared with visual assessment (Fig. 1). Results: LGE was identified in 41 arrhythmic MVP patients (62%) and quantified (Fig. 2). The mean quantity of LGE visually assessed was 2.40±1.07% or 1.40±0.82 g. With FWHM, LGE resulted 3.56±1.23% or 1.99±1.13 g. Using thresholding, the mean LGE quantity was 9.2±3.1% or 4.82±2.28 g for 2-SD, 5.72±1.75% or 3.06±1.47 g for 3-SD and 2.36±0.99% or 1.29±0.79 g for 5-SD. The 5-SD measurement in percentage demonstrated a good correlation with LGE quantification visually assessed (2.402±1.075 vs 2.363±0.9909, p: 0.543). Despite all semi-quantitative methods for LGE quantification demonstrated a good intra and inter-observer agreement, the 5-SD threshold quantification, both in percentage and in grams, revealed the less intra-observer (respectively, ICC: 0.976 and 0.966) and inter-observer variability (respectively ICC: 0.948 and 0.935) when compared with visual assessment. Conclusion: This is the first study that quantified and compared different CMR semi-automated methods for LGE assessment in a population of arrhythmic MVP patients. The 5-SD gray-scale threshold technique in percentage revealed the best correlation with the visual assessment and an optimal reproducibility. Funding Acknowledgement: Type of funding sources: None.